Exemplar of Micro Strategies in Teaching Speaking in Indonesian Context - Assalamah, Tuhfatul Mubarokah (Institut Agama Islam Negeri Palopo, 2024)
The post-method era is currently experiencing a surge in popularity within the realm of English language teaching, particularly in the context of English as a Foreign Language (EFL), such as in Indonesia. Given the crucial role of Speaking as a central element in communication, it requires meticulous attention and instruction in an EFL setting. Teachers play a pivotal role in preparing effective strategies to assist learners in achieving fluency and accuracy in spoken English. Consequently, this paper aims to expound on the recommended micro strategies derived from Kumaravadivelu's post-method framework. It delineates the macro strategies of post-method in English Language Teaching (ELT) as the foundational elements for creating micro strategies tailored to the teaching of Speaking in the Indonesian context. The article outlines ten macro strategies, which include increasing learning opportunities, facilitating negotiated interaction, minimizing perceptual mismatches, activating intuitive heuristics, fostering language awareness, contextualizing linguistic input, integrating language skills, promoting learner autonomy, ensuring social relevance, and raising cultural consciousness. Drawing on this strategic framework, the article gives illustrated instances of classroom activities and instructional tactics, dubbed micro strategies, that have been utilized to improve Indonesian learners' EFL Speaking competency.